Pregnant biglycan knockout mice have altered cardiorenal adaptations and a shorter gestational length, but do not develop a pre-eclamptic phenotype. (4th March 2022) - Briffa, J.F.; Bevens, W.; Gravina, S.; Said, J.M.; Wlodek, M.E.
Abstract: Introduction: Pre-eclampsia complicates 4.6% of pregnancies and is linked to impaired placentation; likely due to dysregulated vasculogenesis/angiogenesis. Proteoglycans, such as biglycan, are located on the endothelial surface of fetal capillaries. Biglycan is reduced in the placenta of pregnancies complicated by fetal growth restriction and pre-eclampsia. Importantly, biglycan stimulates angiogenesis in numerous tissues. Therefore, this study investigated whether biglycan knockdown in mice results in a pre-eclamptic phenotype. Methods: Wild-type (WT) and Bgn - / - mice underwent cardiorenal measurements prior to and during pregnancy. One cohort of mice underwent post-mortem on gestational day 18 (E18) and another cohort underwent post-mortem on postnatal day 1 (PN1), with maternal and offspring tissues of relevance collected. Results: Bgn - / - dams had increased heart rate (+9%, p < 0.037) and reduced systolic (−11%, p < 0.001), diastolic (−15%, p < 0.001), and mean arterial (−12%, p < 0.001) pressures at all ages investigated compared to WT. Additionally, Bgn - / - dams had reduced urine flow rate (−64%, p < 0.001) as well as reduced urinary excretions (−49%, p < 0.004) during late gestation compared to WT. Bgn - / - pups had higher body weight (+8%, p = 0.004; E18 only) and a higher liver-to-brain weight ratio (+43%, p < 0.001). Placental weight was unaltered with only minor changes in vasculogenic and angiogenic gene abundances detected, which did not correlate to changes in protein expression. Discussion: This study demonstrated that total knockdown of biglycan is not associated with features of pre-eclampsia. Highlights: Biglycan is reduced in pre-eclampsia and silencing biglycan impairs angiogenesis. Biglycan knockdown ( Bgn −/− ) alters maternal cardiorenal adaptations to pregnancy. Biglycan deficiency has a protective effect against fetal growth restriction. Minimal changes were observed in markers of placental vasculogenic/angiogenic. Total knockdown of biglycan does not result in a pre-eclamptic phenotype.